Selected Decisions, 20th Ed. 1995 (Annex) November 30, 1995. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper discusses enhanced structural adjustment facility trust-borrowing agreement. The Trustee may make drawings under this agreement at any time during the period from the effective date of this agreement through December 31, 1999, upon giving the Government of Canada at least five business days (Washington, D.C.) notice. If any instalment of principal or interest is not paid to the Government of China within a period of 10 days after its due date, the Trustee shall not make further drawings under this agreement pending consultations with the Government of China on this matter. Upon request, the Trustee shall issue to the Government of China a non-negotiable certificate evidencing its claim on the Trust resulting from a drawing outstanding under this agreement. By agreement between the Government of China and the Trustee, any drawing or part thereof may be repaid by the Trustee at any time in advance of maturity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet